CO2 hydrogenation into methanol: Measurement and correlation of PVT data - Cotabarren, Natalia Soledad (2023)
CO2 hydrogenation for the synthesis of methanol (CH3OH) is an interesting route to mitigate CO2 emissions and promote a sustainable economy considering CO2 capture/utilization and H2 storage. Based on the current industrial methanol production from syngas (H2+CO and minor quantities of CO2 and CH4), CO2 hydrogenation can be carried out in gas-solid catalytic reactors at moderated pressures (5 to 10 MPa) and temperatures between 490 K and 570 K [1]. However, the current industrial method requires a large recycle flow of syngas due to the limited conversion achieved in the reactor. An interesting concept is to apply in situ condensation of methanol or water (subproduct) operating at higher pressures (12, to 20 MPa) without using adsorbents or additional coolers to increase the conversion [2]. Volumetric properties of reaction systems are needed to elucidate kinetic mechanisms and carry out a proper design of these high-pressure continuous reactors, particularly in the reaction system with an in-situ condensation of products. However, scarce experimental PvT data of the system (CO2+H2+CH3OH+H2O) has been reported in the literature in the range of temperature (493.15 K to 563 K) and pressures (70 to 400 bar) of interest to carry out the CO2 hydrogenation [ref]. Modeling accurately the volumetric properties and phase behavior of this supercritical reaction system can be complex due to the asymmetric molecular nature between reactants (CO2/H2) and products (mainly CH3OH and H2O). In this work, we adapted a high pressure/temperature stainless-steel constant volume cell (12.76 cc) to study experimentally the pressure-temperature isochoric behavior of synthetic mixtures formed by CO2+H2+Methanol+water under different stoichiometric molar ratios. We report new experimental PvT data of non-reactive mixtures of H2+CO2+CH3OH+H2O in the range of temperature and pressure of industrial interest. Also, the phase equilibria and PvT data are modeled using RK-PR, a three-parameter equation of state. We selected the RK-PR because of its simplicity and proven accuracy to represent volumetric properties [3].The apparatus used for performing the PvT measurements operates according to a synthetic method being possible to feed properly known compositions of the system under study. CH3OH/H2O mixtures are injected as liquid in first place, and a high-pressure gas-dosing injection device built in our workshop is used to load CO2/H2 mixtures of known composition. The equipment has been calibrated in the range of operating conditions using pure fluids (methanol, CO2, water). These measurements were compared to PvT data from the National Institute of Standard and Technology (NIST). The uncertainty in the density values is about 1.2 % based on calibration studies. Isochoric studies of the multicomponent system between 0.08 g/cc and 0.5 g/cc show evidence of the phase transition, from heterogeneous to homogeneous, phase condition.